IMPLEMENTATION OF ONLINE LEARNING FOR ENGLISH CLASS DURING COVID-19 PANDEMIC: LEARNERS’ PERCEPTION - Marcela, Eny Dwi; Hastomo, Tommy; Wibowo, Siswo Edi; Damiri, Adenan (STKIP PGRI Bandar Lampung, 2021)
This study aims to identify the learner's perception regarding online learning implementation during the COVID-19 pandemic. Data collection was done through a survey questionnaire consisting of both open-ended and close-ended questions, and continued by interview activities. The participants in this study amounted to 28 students of 3rd semester of STKIP PGRI Bandar Lampung. Data collection techniques in this study used questionnaires with Likert scale and interview. Results from this research showed that students have a positive attitude toward the online learning experience in general. The implementation of online learning during a pandemic is considered an effective and cheap way of accessing knowledge. However, most students showed frustration due to bad internet access, which affects their learning success. Students also felt the need for improvement in terms of interaction and engagement between students and teachers.